Determinan Risiko Terjadinya Gangguan Makan pada Remaja di SMAN 7 Tangerang Tahun 2025: Determinants of Eating Disorders Risk in Adolescents at SMAN 7 Tangerang, 2025 - Ghefira Tsana Zahirah; Firlia Ayu Arini; Sintha Fransiske Simanungkalit (Amerta Nutrition, 2025)
Background: Eating disorders are a serious problem experienced by many adolescents, characterized by unhealthy eating behaviors due to dissatisfaction with body image and aimed at achieving an ideal body. Adolescence represents a critical developmental stage characterized by identity formation and heightened susceptibility to social pressures, including idealized body standards promoted through social media. The widespread use of social media and environmental influences exacerbate the risk of developing eating disorders. Objectives: This study sought to examine the association between gender, body image perception, nutritional status, intensity of social media use, celebrity worship, and nutrition knowledge with the risk of eating disorders among students at SMAN 7 Tangerang in 2025. Methods: A cross-sectional study design utilizing proportionate stratified random sampling was conducted with 150 participants. Data were collected through the administration of structured questionnaires via Google Forms and anthropometric measurements to assess nutritional status. Results: The findings indicated no significant relationship between gender (p-value=0.148), nutritional status (p-value=0.241), social media usage intensity (p-value=0.808), celebrity worship (p-value=0.279), and nutrition knowledge (p-value=0.193) with the risk of eating disorders. However, a significant relationship was found between body image perception (p-value<0.001) and the risk of eating disorders, with an odds ratio of 4.854 (95% CI=2.093-11.257). Conclusions: Body image perception demonstrates a significant relationship with eating disorders risk among adolescents at SMAN 7 Tangerang in 2025 (OR=4.854; 95% CI=2.093-11.257).